Assessing the impact of community extension program in a Philippines state university: A comprehensive framework and analysis - Esteban, Allen Paul (Edelweiss Applied Science and Technology, 2025)
This paper aimed to assess the impact of the implemented extension program of the Graduate School of Nueva Ecija University of Science and Technology in different partner communities. It also determined the number of program outputs; the impact of each output in terms of Satisfaction, Effectiveness, Relevance, and Impact (SERI) and its sustainability. It sought to understand the organizational, external, and individual impact and propose recommendations to enhance the delivery of the community extension program. This sequential explanatory mixed-method study used survey methods, narrative, and content analysis validated by internal and external groups and individuals. Qualitative findings reveal themes such as Successful Implementation with Limited Continuity, Hardware/Resource Limitation, and Knowledge Application, highlighting both successes and challenges in project execution. Concurrently, the quantitative data provide insights into client satisfaction, effectiveness, relevance, and impact across different projects, highlighting notable achievements alongside areas for improvement. A comprehensive analysis revealed that despite facing challenges amidst the pandemic, the program demonstrated significant outcomes and impacts in the partner communities. With 15 extension projects, it addresses community needs and promotes development. SERI criteria rated the program 3.33, indicating "Some Evidence of Impact" with short-term sustainability. Relevance was the highest rate among the criteria. Despite encountering challenges such as budget utilization issues and sustainability concerns, the programs demonstrate significant impacts, including increased productivity, cost savings, and skill development among participants. This research provides valuable insights for program improvement and emphasizes the importance of holistic approaches to community engagement and development.